Wordwide patterns of genetic differentiation imply multiple ‘domestications’of Aedes aegypti, a major vector of human diseases - Brown, Julia E.; McBride, Carolyn S.; Johnson, Petrina; Ritchie, Scott; Paupy, Christophe; Bossin, Herve; Lutomiah, Joel; Fernández Salas, Ildefonso; Ponlawat, A.; Cornel, A. J.; Black, William C.; Gorrochótegui Escalante, Norma; et al. (2011)
Understanding the processes by which species colonize and adapt to human habitats is particularly important in the case of disease-vectoring arthropods. The mosquito species Aedes aegypti, a major vector of dengue and yellow fever viruses, probably originated as a wild, zoophilic species in sub-Saharan Africa, where some populations still breed in tree holes in forested habitats. Many populations of the species, however, have evolved to thrive in human habitats and to bite humans. This includes some populations within Africa as well as almost all those outside Africa. It is not clear whether all domestic populations are genetically related and represent a single ‘domestication’ event, or whether association with human habitats has developed multiple times independently within the species. To test the hypotheses above, we screened 24 worldwide population samples of Ae. aegypti at 12 polymorphic microsatellite loci. We identified two distinct genetic clusters: one included all domestic populations outside of Africa and the other included both domestic and forest populations within Africa. This suggests that human association in Africa occurred independently from that in domestic populations across the rest of the world. Additionally, measures of genetic diversity support Ae. aegypti in Africa as the ancestral form of the species. Individuals from domestic populations outside Africa can reliably be assigned back to their population of origin, which will help determine the origins of new introductions of Ae. aegypti.